2018
DOI: 10.1108/ijm-01-2017-0011
|View full text |Cite
|
Sign up to set email alerts
|

Is too much inclusive leadership a good thing? An examination of curvilinear relationship between inclusive leadership and employees’ task performance

Abstract: Purpose The purpose of this paper is to examine the inclusive leadership’s too-much-of-a-good-thing effect (TMGT effect) and illustrate the possibility of the potential drawbacks of inclusive leadership. Design/methodology/approach In total, 191 questionnaires were valid and used in the study. Employee participants were asked to report their direct supervisor’s inclusive leadership. Employees’ direct supervisors were asked to rate employees’ task performance to minimize common method variance. The authors us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 48 publications
0
30
0
3
Order By: Relevance
“…Frost (2018) found that the combination of inclusive leadership and diverse teams can promote innovation. However, as is known to all in China, "a kind mother makes a wastrel, " some scholars have begun to argue that inclusive leadership also has the negative impact on employees' behavior (Gu et al, 2017), which have been proved by some recent empirical studies (Zheng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Frost (2018) found that the combination of inclusive leadership and diverse teams can promote innovation. However, as is known to all in China, "a kind mother makes a wastrel, " some scholars have begun to argue that inclusive leadership also has the negative impact on employees' behavior (Gu et al, 2017), which have been proved by some recent empirical studies (Zheng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This is because employees who are tightly controlled, implying not having much autonomy and not involved in making choices feel vulnerable and threatened resulting in disengagement (Pech, 2009). This explains why having autonomy has been cited as an antecedent to engagement (Christian et al., 2011) and including followers as antecedents to ETP (Xiaotao et al., 2018). Accordingly, when subordinates are assigned responsibility and given some form of autonomy, it causes them to be engaged, leading to the employees putting in extra, working with vigor, being more dedicated, getting more absorbed as they work, and this affect their level of performance positively.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Saz-Carranza and Ospina (2011) described that an inclusive leader is valuable, and is someone who accepts staff at all levels in the organization and is responsible for results. Furthermore, in the context of Chinese culture, inclusive leadership not only accepts and respects employee differences, recognizes employee effort and value, and encourages employee participation, but also accommodates employee error (Zheng et al, 2018). Compared with the other conceptually related forms of leadership, inclusive leadership holds a unique nature of acceptance, belongingness, uniqueness, and inclusiveness (Randel et al, 2017).…”
Section: Theoretical Background and Hypotheses Inclusive Leadership And Employee Innovative Behaviormentioning
confidence: 99%